MEMBANGUN PERSONAL BRANDING DAN KEMAMPUAN PUBLIC SPEAKING UNTUK PENGEMBANGAN KARIR MASA DEPAN PEMUDA - Ahmad Anif Syaifudin; Sutin Narto (ABDI MAKARTI, 2023)
Indonesia has a demographic bonus in 2045. This opportunity is projected to be a golden period where there are many opportunities, potential, and opportunities for people in their careers. To welcome the demographic bonus, planning training that can develop the community, namely public speaking and personal branding skills is necessary. Personal branding and public speaking are personal competencies that need to be developed in facing the challenges of an increasingly competitive world of work. This activity aims to improve partners' skills in presentation, speech, MC, and communicating effectively. While the skills of building a self-image (personal branding) are a way for partners to market themselves to be recognized by others. The methods used include 1) analysis of partner needs as a benchmark for ability and material limits, 2) training and mentoring of partners which is the core of the program, where partners are provided with material on public speaking and personal branding techniques. The results of this service show that partners are able to plan how to brand themselves with self-promotion. In addition, partners are more confident in speaking in public. This can be seen from the enthusiasm of the partners when practicing as master of ceremony and speakers on stage.